Climate control on the palaeo-lake evolution in the southern Datong Basin, North China: Evidence from 800-ka core records. (10th July 2015) - Gu, Yansheng; Hong, Hanlie; Xie, Xianjun; Wang, Yanxin
Abstract: Integrated sedimentological and clay mineral analyses of a 300-m-depth core reveal the history of the palaeo-lake and palaeoclimatic evolution of the southern Datong Basin over the past 800 ka. The sedimentary facies, including deep lake, shallow lake, alternation of lakeside and shallow lake, and the river environment are identified based on the general characteristics of the grain size analysis. Two episodes of warm–humid events are responsible for the palaeo-lake expansion during the period of 800–480 ka, corresponding to the presence of S7, S6, and S5 in the Loess Plateau. A stepwise cooling and drying trend since approximately 480 ka is strongly linked to the gradual shrinkage and extinction of the palaeo-lake. Our results demonstrated that climate change has played an essential role on the palaeo-lake expansion/shrinkage during the Middle Pleistocene. Breaching of Shixia Gorge by active neotectonic movement since the middle Late Pleistocene enhanced the shrinkage and extinction of the palaeo-lake, coupled with a cold–dry climate in the Last Glacial. The climatic changes documented by clay minerals and grain size parameters in the Datong Basin are consistent with the loess–paleosol sequences in the Loess Plateau and fluvio-lacustrine sediments in the Nihewan Basin, mainly controlled by the East Asian Monsoon in response to the regional global change since the Mid-Late Pleistocene.